Time to simplify banking supervision: An evidence-based study on PCA framework in India - Soumik Bhusan; Angshuman Hazarika; Naresh Gopal (Journal of Risk and Financial Management, 2022)
The financial stability of the commercial banking sector remains one of the critical responsibilities of the Reserve Bank of India (RBI). Weak banks cause instability in the financial system, triggering depositor runs. While several studies covered the prompt corrective action framework (PCA) for identifying weak banks, very few delve into the simplification of the same. This paper debates the opportunities to simplify using new parameters that reflect signs of weakness in a commercial bank. The PCA framework introduced in December 2002 marked a paradigm shift in the RBI's supervision mechanism. At its inception, the RBI used three parameters (capital to risk-weighted assets, net non-performing assets, and return on assets) to identify weak banks. In 2017, the RBI added two more parameters (tier-1 leverage, common tier-1 equity) to build rigour in the framework. Banks that breach the threshold in any of these financial parameters could come under the RBI's lenses. Under such a situation, the bank has to operate under constraints imposed on expansion, managerial compensation, raising deposits, and dividends distribution. This article explores new ratios and establishes their application in PCA using "linear discriminant analysis". We debate reducing the number of parameters from five to two, and conclude that only coverage ratio (new) and credit-to-deposit ratio (new) could simplify PCA without diluting its effectiveness.
Keywords: 650; banking supervision; India; PCA framework; RBI; weak commercial banks